The Varieties of Ecological Rationality in Decision Making and Their Challenge to Behavioral Economics. - FOKA-KAVALIERAKI, YULIE (Independent Review)
The article focuses on the concept of ecological rationality and its varied interpretations across different academic disciplines studying decision-making and problem-solving. Topics include the diverse fields contributing to ecological rationality, the challenge it poses to the heuristics-and-biases project initiated by Kahneman and Tversky, and the underlying principles of evolutionary theory that unite these approaches in understanding behavior as a response to environmental contexts.